Postglacial paleoceanography and paleoenvironments in the northwestern Barents Sea - Ivanova, Elena; Murdmaa, Ivar; De Vernal, Anne; Risebrobakken, Bjørg; Peyve, Alexander; Brice, Camille; Seitkalieva, Elvira; Pisarev, Sergey (Quaternary Research, 2019)
Abstract The Barents Sea offers a suitable location for documenting advection of warm and saline Atlantic Water (AW) into the Arctic and its impact on deglaciation and postglacial conditions. We investigate the timing, succession, and mechanisms of the transition from proximal glaciomarine to marine environment in the northwestern Barents Sea. Two studied sediment cores demonstrate diachronous retreat of the grounded ice sheet from the Kvitøya Trough (core S2528) to Erik Eriksen Trough (core S2519). Oxygen isotope records from core S2528 depict a two-step pattern, with lower δ 18 O values prior to the Younger Dryas (YD), and higher values afterward because of advection of the more saline, 18 O-enriched AW. At this location, subsurface AW penetration increased during the Allerød and YD/Preboreal transition. In the study area, foraminiferal and dinocyst data from the YD interval suggest cold conditions, extensive sea-ice cover, and brine formation, along with the flow of chilled AW at subsurface and the development of a high-productivity polynya in the Erik Eriksen Trough. Dense winter sea-ice cover with seasonal productivity persisted in the Kvitøya Trough area during the early Holocene, whereas surface warming seems to have occurred during the middle Holocene interval.